2019
DOI: 10.31339/2313-8114-2019-2(12)-33-39
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study of the Nervous-Psychic Resistance of Students of Humanities and Economic Specialties

Abstract: Ліба Наталія Степанівна, д.е.н., доцент кафедри обліку і оподаткування та маркетингу, Мукачівський державний університет Марценюк Марина Олексіївна, к. соц.н., старший викладач кафедри психології, Мукачівський державний університет, Медвідь Лариса Іванівна, старший викладач кафедри туризму і географії, Мукачівський державний університет ЕМПІРИЧНЕ ДОСЛІДЖЕННЯ НЕРВОВО-ПСИХІЧНОЇ СТІЙКОСТІ СТУДЕНТСЬКОЇ МОЛОДІ ГУМАНІТАРНИХ ТА ЕКОНОМІЧНИХ СПЕЦІАЛЬНОСТЕЙ Сучасний стан розвитку суспільства, який проходить у складних і… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These initiatives have been developed to raise awareness about safety and improve risk perception among all workers. In a company with a management system for occupational safety and security, risk management activities developed by the organization, optimized, for example, inspection workplace, risk assessment, risk control, risk reporting and consultation, accident registration and analysis, and training safety (Liba et al, 2019;Hryshchuk, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These initiatives have been developed to raise awareness about safety and improve risk perception among all workers. In a company with a management system for occupational safety and security, risk management activities developed by the organization, optimized, for example, inspection workplace, risk assessment, risk control, risk reporting and consultation, accident registration and analysis, and training safety (Liba et al, 2019;Hryshchuk, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Students' satisfaction is a complex and multifactorial concept that provides valuable data for colleges and universities to make their curriculum more responsive to the needs of a changing marketplace (Witowski, 2008;Eyck et al, 2009;Papathanasiou et al, 2014;Liba et al, 2019). The assessment of nursing students' satisfaction in the current study showed moderate overall satisfaction with higher levels regarding the program design and delivery, where student were relatively more students perceived courses to be beneficial in enhancing their overall professional development and analytical skills and were satisfied with the variety and relevance offered by the faculty's program.…”
Section: Resultsmentioning
confidence: 99%